Mitochondria-Targeted Honokiol Confers a Striking Inhibitory Effect on Lung Cancer via Inhibiting Complex I Activity - Pan, Jing; Lee, Yongik; Cheng, Gang; Zielonka, Jacek; Zhang, Qi; Bajzikova, Martina; Xiong, Donghai; Tsaih, Shirng-Wern; Hardy, Micael; Flister, Michael; Olsen, Christopher M; Wang, Yian; et al. (iScience, 2018)
We synthesized a mitochondria-targeted honokiol (Mito-HNK) that facilitates its mitochondrial accumulation; this dramatically increases its potency and efficacy against highly metastatic lung cancer lines in vitro, and in orthotopic lung tumor xenografts and brain metastases in vivo. Mito-HNK is >100-fold more potent than HNK in inhibiting cell proliferation, inhibiting mitochondrial complex ?, stimulating reactive oxygen species generation, oxidizing mitochondrial peroxiredoxin-3, and suppressing the phosphorylation of mitoSTAT3. Within lung cancer brain metastases in mice, Mito-HNK induced the mediators of cell death and decreased the pathways that support invasion and proliferation. In contrast, in the non-malignant stroma, Mito-HNK suppressed pathways that support metastatic lesions, including those involved in inflammation and angiogenesis. Mito-HNK showed no toxicity and targets the metabolic vulnerabilities of primary and metastatic lung cancers. Its pronounced anti-invasive and anti-metastatic effects in the brain are particularly intriguing given the paucity of treatment options for such patients either alone or in combination with standard chemotherapeutics.
Keywords: Natural Product Chemistry; Medicinal and Aromatic Plants; Immunology